2017
DOI: 10.1016/j.omtm.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Vero-Based Packaging Cell Line to Produce SV40 Gene Delivery Vectors for Use in Clinical Gene Therapy Studies

Abstract: Replication-defective (RD) recombinant simian virus 40 (SV40)-based gene delivery vectors hold a great potential for clinical applications because of their presumed non-immunogenicity and capacity to induce immune tolerance to the transgene products in humans. However, the clinical use of SV40 vectors has been hampered by the lack of a packaging cell line that produces replication-competent (RC) free SV40 particles in the vector production process. To solve this problem, we have adapted the current SV40 vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
(54 reference statements)
0
19
0
Order By: Relevance
“…Clinical studies revealed that because of the immune memory in humans, the in vivo efficacy of AAV vectors is very low. SV40 vectors are the only gene delivery vectors that can be used for inducing immune tolerance to transgene proteins in humans and for this reason the oldest viral gene delivery vector will be key to the successful development of effective interventions for today’s major diseases ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies revealed that because of the immune memory in humans, the in vivo efficacy of AAV vectors is very low. SV40 vectors are the only gene delivery vectors that can be used for inducing immune tolerance to transgene proteins in humans and for this reason the oldest viral gene delivery vector will be key to the successful development of effective interventions for today’s major diseases ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, an SV40 vector destination plasmid pSV ac was used, in which the vector genome is flanked by Lox-P sites to allow specific removal of the bacterial backbone by Cre recombinase expressed in SV40 vector packaging cells. 36 We here show that expression of Cre recombinase in COS-1 and SuperVero cells results in an efficient removal of the bacterial backbone.…”
Section: Introductionmentioning
confidence: 70%
“…COS-1 cells were transfected with the following: (1) the rSV Luc 36 plasmid with Lox-P sites flanking the rSV genome; (2) the rSV LucΔLox-P plasmid without Lox-P site co-transfected with a Cre-expressing plasmid; and, (3) as a negative control, a GFP-expressing plasmid. At 5 days after transfection, the medium was harvested and the titer of rSV Luc was determined using qPCR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations